Sweet waste extract uptake by a mosquito vector: Survival, biting,fecundity responses, and potential epidemiological significance - Hamady, Dieng; Satho, Tomomitsu; Fatimah, Abang; Nur Khairatun Khadijah, Binti Meli; Idris, Abd Ghani; Cirilo Nolasco, Nolasco-Hipólito; Hafijah, Hakim; Miake, Fumio; Abu Hassan, Ahmad; Sabina, Noor; Gabriel Tonga, Noweg; Wan Fatma, Zuharah; et al. (Elsevier, 2017)
tIn nature, adult mosquitoes typically utilize nectar as their main energy source, but they can switch toother as yet unidentified sugary fluids. Contemporary lifestyles, with their associated unwillingness toconsume leftovers and improper disposal of waste, have resulted in the disposal of huge amounts of wasteinto the environment. Such refuse often contains unfinished food items, many of which contain sugarand some of which can collect water from rain and generate juices. Despite evidence that mosquitoescan feed on sugar-rich suspensions, semi-liquids, and decaying fruits, which can be abundant in garbagesites, the impacts of sweet waste fluids on dengue vectors are unknown. Here, we investigated the effectsof extracts from some familiar sweet home waste items on key components of vectorial capacity ofAedes aegypti. Adult mosquitoes were fed one of five diets in this study: water (WAT); sucrose (SUG);bakery product (remnant of chocolate cake, BAK); dairy product (yogurt, YOG); and fruit (banana (BAN).Differences in survival, response time to host, and egg production were examined between groups. Forboth males and females, maintenance on BAK extract resulted in marked survival levels that were similarto those seen with SUG. Sweet waste extracts provided better substrates for survival compared to water,but this superiority was mostly seen with BAK. Females maintained on BAK, YOG, and BAN exhibitedshorter response times to a host compared to their counterparts maintained on SUG. The levels of eggproduction were equivalent in waste extract- and SUG-fed females. The findings presented here illustratethe potential of sweet waste-derived fluids to contribute to the vectorial capacity of dengue vectors andsuggest the necessity of readdressing the issue of waste disposal, especially that of unfinished sweetfoods. Such approaches can be particularly relevant in dengue endemic areas where rainfall is frequentand waste collection infrequent.